Post-buckling behaviour study of a miniature bar-typed steel fuse with IM-isotropous sections. (January 2023) - Yang, Sen; Liu, Wen-Guang; Guan, Dongzhi; Ge, Hanbin; Guo, Zhengxing
Abstract: In this paper, the mechanical behaviour of a miniature bar-typed steel fuse (MBSF) was studied. The fuse consists of a section-weakened core bar and a confined tube and can serve as the energy dissipation element in structures. Per the preliminary studies, the specimens with an isotropous inertia-moment (IM) core bar were deeply influenced by the spatial compressive buckling effect, which required a more precise analytical method. To elucidate the inherent mechanical principle, four specimens with IM-isotropous sections of triple and circular-line cutting (TC and CC) were produced and subjected to reversed cyclic loading tests. Then, the FEM and theoretical analyses were conducted correspondingly. The results proved a helix buckling mode in the IM-isotropous sectional specimens and the simplified analytical models were established to predict the contact effects of the core bar and the confined tube. The established method achieved good accuracy with the experimental results. Highlights: A miniature bar-typed steel fuses with isotropous inertia-moment sections were studied experimentally and numerically. Four specimens with triple and circular-line cutting sections were involved and presented good damper capacities. A helix post-buckling behaviors were determined for the two IM-isotropous MBSFs. Two analytical methods based on the small lateral deformation hypothesis were proposed and achieved sufficient accuracy.